Need for Journal Analysis: Is Citation-Based Scores Good Enough to Rank a Journal? - Jitendra D. Lakhani; Niraj Pandit; Girish Sailor (Journal of Integrated Health Sciences)
Journal analysis denotes evaluation, assessment, ranking, and scoring of a journal. It is an important exercise to be adopted by learning resource organization for recommending a journal for referring, scanning, referencing, subscribing, publishing, circulating, and disseminating purposes. Evaluation is done qualitatively in relation to content, objectives, and ethos. Rhetorical analysis of a journal will take into account something which is abstract and nonliteral. Advancement in ideology, in relation to different sphere of academic domains, is important key element of a particular journal. Journal which may communicate theory, practice, methods, skills, and thought process as a whole can reflect the image of an excellent journal. Analysis of these qualitative aspects should be part of the journal analysis. Quantitatively it can be ranked by modern tools which started as Science Citation Index and impact factor (IF) which then progressed to other numerical integers such as Eigenfactor score, Article Influence Score, and others. Numerical IFs have led to ranking system of journals and are based on “citations.” Can “citations” and its resultant statistics measure true impact of a journal? This article tries to share their viewpoint with discussion on various aspects of journal analysis.